Effective Strategies for Shaping Students’ Discipline by English Teachers at SMPN 3 Polewali - Annisa, Andi Nur; Noni, Nurdin; Talib, Ahmad (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2025)
This study examined the strategies used by English teachers to shape student discipline at SMPN 3 Polewali, focusing on methods such as self-directed, student-directed, and situation-directed strategies, as well as rewards and punishments. Using a descriptive qualitative approach, data were collected through classroom observations, teacher interviews, and documentation. The findings revealed that teachers involved students in creating classroom rules, fostering a sense of responsibility. Positive reinforcement, including praise and additional grades, effectively motivated students, while non-verbal cues like eye contact helped maintain classroom order. Teachers also used specific punishments, such as vocabulary memorization, for recurrent discipline issues. Among these methods, reward strategies proved to be the most influential in encouraging student discipline, as they fostered intrinsic motivation and reinforced positive behavior in a conducive learning environment.